Adaptive coordinated motion control with variable forgetting factor for a dual-arm space robot in post-capture of a noncooperative target. (13th September 2019) - Jiao, Chunting; Yang, Jun; Wang, Xueqian; Liang, Bin
To overcome the problem of dynamics coupling between a space robot and a target satellite, this study introduces a new coordinated motion control approach with an adaptive filtering algorithm for a dual-arm free-floating space robot. Based on the reaction null space control scheme, one arm is used to complete the capture task and the other to counteract disturbance to the space base. However, when space robot captures a noncooperative target, the system may experience abrupt changes in dynamic parameters and output measurement noise, which can cause traditional control methods to achieve poor results in practical applications. Thus, an adaptive filtering algorithm with a variable forgetting factor is proposed to improve the tracking capabilities and robustness of the system. The convergence analysis is performed based on a Lyapunov function. The simulation results demonstrate the effectiveness of the proposed algorithm.